Accounting Information System and Effective Leadership to Improve Employee Performance - Sari, Nur Zeina Maya; Johan, Ahmad; Pramiarsih, Euis Eka (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
Accounting information system and effective leadership already implemented and running with good can increase performance employees at Inspectorate general office regency Bandung. Method research used that is descriptive and verifiable with approach quantitative. Population in study This is all staff of Inspectorate general office which consists of on employee department accounting. Probability sampling techniques with use random sampling so that amount sample in study This determined a total of 33 data sources were obtained originate from distribution questionnaire. Data in study This is primary data using questionnaire. Research this also uses method analysis descriptive and verifiable as well as approach processed quantitative in a way structured use SEM-PLS. Results from study This show that 1) Success system information accounting is very high 2) Success System Information Accountancy influential to performance employees 3 ) Effective leadership in category enough height and 4) Leadership influential to performance.